Asymmetric Cost Behavior In Indonesia - Muh. Pungki Nur Setiawan; Nur Aisyah Kustiani; Intan Dwi Puspitasari (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Let’s say that last year’s sales had a 1% increase and expenses had a 0.53% increase compared to the year prior. If this year's sales decrease by 1%, how much will the expenses decrease? Most of us will answer that the expenses will decrease symmetrically, which is around 0.53%. However, this study finds that expenses increase by 0.53% per 1% increase in sales but only decrease by 0.39% per 1% decrease in sales. This phenomenon is called